The utilisation of games technology for environmental design education - Sarhan, Ahmed (2012)
In recent years, the architectural design process has witnessed a mounting demand for qualified practitioners who can resolve the highly complex social, cultural, technological, and economical issues associated with ‘Sustainability’. Designers are thus faced with wider pallet of challenges, developing conceptual designs that are sustainably effective. Pressure is mounting on educational institutions to prepare architects that are well accustomed to the environmental design concepts and parameters, aiming to reduce the impact on the environment and preserve valuable natural resources to bring the building’s interior to comfortable living conditions. However, architectural education has been notably slow to respond effectively to the requirements introduced by sustainability. Evidently there are a number of pedagogical challenges that clearly impede the consistent endorsement of sustainability in the design curricula and thus hinder any potential values and opportunities that can result from its effective integration.